Teaching L2 Galician through the traditional songbooks: The case of the direct object [+human] with the preposition a - Sánchez Rei, Xosé Manuel (Glottodidactica, 2023)
Explaining the grammatical structures that characterize the Galician language system to university students of L2 Galician involves certain difficulties, both in terms of contact with Spanish and due to its nature as an L2 language. It must be noted that such learners’ L1 is mostly Spanish, French, English or Italian. We propose in this paper an activity in which students engage in a process of practical reflection on real examples of the language. The activity will focus in par-ticular on the absence of the preposition a with the direct object (DO), i.e., Nós saudamos o teu amigo (“We greet your friend”), using for this purpose a corpus of traditional Galician popular songs, and following the recommendations of the Content and Language Integrated Learning (CLIL) model. Within this theoretical and practical approach students will also acquire knowledge of Galician culture and history, through information found in the anonymous poetry of the songbook itself.